Comparative analysis of the nutritional, biochemical and hematological parameters of pregnant women attending the University of Abuja Teaching Hospital, Nigeria - Emeribe, Anthony Uchenna; Dangana, Amos; Isa, Hezekiah Alkali; Onoja, Solomon Elochi; Otu, Theresa Ohunene; Ibrahim, Yakubu; Mohammad Jamil, Amilia Afzan; Lugos, Moses D.; Aliyu, Dorcas; Haruna, Shamsudeen; Mallam, Mala Alhaji Baba; Yahaya, Hadiza; et al. (China Medical University, 2022)
Background: Despite the efforts to encourage the intake of nutritional supplements during antenatal periods, there are still many cases of anemia and protein-energy malnutrition during pregnancy. Hence, this study determined the incidence of anemia, protein-energy malnutrition, and associated risk factors among pregnant women in Abuja, Nigeria. Materials and Methods: This hospital-based, case-control study involved randomly selected 176 pregnant and non-pregnant women attending the University of Abuja Teaching Hospital (UATH), Gwagwalada, Nigeria. Hemoglobin and hematocrit measurements were used to determine anemia incidence, while plasma protein, zinc levels and body mass index (BMI) were used to determine energy index status. Complete blood counts were analyzed using 5 parts-automatic hemo-analyzer, while plasma protein and zinc were analyzed using calorimetric method. Anemia and protein-energy malnutrition were defined using the World Health Organization (WHO) cut-off values. Results: The mean age of participants was 28.75 ± 5.22 years. Out of 176 participants, 7 (4%) were malnourished while 25% of the participants were anemic. Anemia was significantly associated with participants’ occupation (p=0.002), parity (p˂0.001) and gestational age (p˂0.001). Most hematological indices, plasma globulin, albumin, protein, and zinc levels were significantly different (p˂0.001) among non-pregnant and pregnant women of the first, second and third trimesters. Conclusion: The incidence of anemia and malnutrition was high among study participants. There is a need for improved nutritional intervention, increased awareness and strengthening of health systems in the area of maternal health in Nigeria.